Islamic Banks and Monetary Variables in Indonesia - Sari, Rahma; Subagya, Denysa Cristiana; Laela, Khusnul; Ridani, Fara; Kurniawan, Mahrus Lutfi Adi (Journal of Islamic Economics and Philanthropy, 2024)
The pattern of sharia banking which is different from conventional banks can be seen during the crisis, where sharia banking is procyclical during the crisis and countercyclical during the expansion period, this shows that sharia banking prevents a worse crisis from occurring. This pattern must be balanced with caution in implementing monetary policy, because monetary policy is very closely related to the financial sector, including the sharia financial sector. This research aims to analyze monetary variables on sharia banking financing. Monetary variables used include the BI rate, money supply, exchange rate, production index as a proxy for GDP and inflation. The research use time-series data and the OLS method. The research result show that monetary variables have a significant effect on sharia banking financing. This research implication is that the monetary policy implemented focuses on price stability and the domestic economy to support the growth of sharia banking financing.